DAMPAK KOMUNIKASI DIGITAL TERHADAP DUNIA PENDIDIKAN (Studi Empiris pada Institusi Pendidikan di Indonesia Pasca-Pandemi COVID-19): Digital Communication, Digital Education, Digital Transformation, Learning Effectiveness - Sania Davina Putri; Sarmini; Sri Yanti; Ngaliman; Mardiana (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2026)
This study aims to analyze the impact of digital communication on education in Indonesia, particularly in the post-COVID-19 pandemic context, which has accelerated digital transformation. Digital communication has become a key element in the learning process, academic interactions, and information management between teachers, students, and institutions. This study used a descriptive quantitative approach, distributing questionnaires to 320 respondents (teachers and students) from various educational institutions in Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that digital communication had a positive and significant effect on learning effectiveness (β = 0.476; p < 0.001) and academic collaboration (β = 0.512; p < 0.001). These findings suggest that the implementation of structured digital communication can improve student participation, engagement, and learning outcomes.